More on 1QSamuel and the Theory of Literary Growth. Response to Benjamin Ziemer - Elgvin, Torleif (Zeitschrift für die alttestamentliche Wissenschaft, 2021)
There is no space in the innermost part of the 1QSam scroll to include 2Sam 24. The last three columns (2Sam 20-23) can be materially reconstructed with 46, 42, or 21 lines. With one of the eight literary appendices to 2Samuel missing, other appendices may be absent too. A number of factors point to a reconstruction with 21 lines and containing only three appendices: a) very few scrolls dated to 50-1 BCE have more than 40 lines, medium-sized scrolls are most common; b) a 46-line reconstruction without ch. 24 would destroy the chiastic structure of the appendices; c) a 46-line reconstruction (as preferred by Ziemer) would require the long psalm of ch. 22 to be formatted without any section breaks or vacat s; d) Qumran scrolls and literary analysis evince many cases of 2 nd and 1 st century literary editing of biblical scrolls as well as preservation of earlier variant recensions. Further, Ziemer’s consequent critique of the linear model of literary growth in biblical studies should be welcomed but remains one-sided. Editorial growth into new recensions could develop according to different paradigms.